Assessing Racial Disparities in Homicide Sentencing: Findings From Brazil. Issue 9 (May 2023) - Testa, Alexander; Santos, Mateus Rennó; Ribeiro, Ludmila; Hartley, Richard
Over the past four decades, hundreds of studies have examined the presence of racial disparities in criminal punishment. The bulk of this research has been conducted in the United States and a few other western democracies, with limited research assessing the presence of racial disparities in criminal sentencing for homicides in South America. Using information gathered via original data collection on homicide cases from five different capital cities in Brazil, the current study examines two criminal court outcomes: whether a defendant was convicted and the length of sentence. Findings reveal the absence of racial disparities in conviction decisions, even though Black and Brown defendants received longer sentence lengths. Supplementary analyses show racial disparities in sentence length are most pronounced when the homicide victim was White. Implications for studying court outcomes in international contexts are discussed.